VII Latin Ibero-American Seminar Of The Technological Management Association (ALTEC), 2020 Venezuelan Edition "Intellectual property in technology management" (Gestión y Gerencia, 2020)
The objective of this report is to succinctly present the activities carried out at the VII Latin Ibero-American Association of Technological Management Seminar, (ALTEC), Venezuela 2020 Edition and organized by the University of Carabobo the week of November 23 to 27, 2020, under the title "Intellectual property in technological management". The pandemic generated by COVID 19 led to the Seminar being held online. During its development, visions, knowledge and experiences of 15 national and international guests were shared. Holding this type of event supports the dissemination of knowledge about Technological Management. At the close, the baton was passed to the Sarteneja Technological Park of the Simón Bolívar University, where the VIII Seminar will be held in 2022.
Keywords: Seminar VII ALTEC Venezuela Edition; Universidad de Carabobo; intellectual property